Contrasting effects of whole-body and hepatocyte-specific deletion of the RNA polymerase III repressor Maf1 in the mouse - Willemin, Gilles; Mange, François; Praz, Viviane; Lorrain, Séverine; Cousin, Pascal; Roger, Catherine; Willis, Ian M.; Hernandez, Nouria (Frontiers in Molecular Biosciences, 2023)
MAF1 is a nutrient-sensitive, TORC1-regulated repressor of RNA polymerase III (Pol III). MAF1 downregulation leads to increased lipogenesis in D. melanogaster, C. elegans, and mice. However, Maf1 -/-mice are lean as increased lipogenesis is counterbalanced by futile pre-tRNA synthesis and degradation, resulting in increased energy expenditure. We compared Chow-fed Maf1 -/-mice with Chow-or High Fat (HF)-fed Maf1 hep-/-mice that lack MAF1 specifically in the liver. Unlike Maf1 -/- mice, Maf1 hep-/-mice become heavier and fattier than control mice with old age and much earlier under a HF diet. Liver ChIPseq, RNAseq and proteomics analyses indicate increased Pol III occupancy at Pol III genes, very few differences in mRNA accumulation, and protein accumulation changes consistent with increased lipogenesis. Futile pre-tRNA synthesis and degradation in the liver, as likely occurs in Maf1 hep-/-mice, thus seems insufficient to counteract increased lipogenesis. Indeed, RNAseq and metabolite profiling indicate that liver phenotypes of Maf1 -/-mice are strongly influenced by systemic inter-organ communication. Among common changes in the three phenotypically distinct cohorts, Angiogenin downregulation is likely linked to increased Pol III occupancy of tRNA genes in the Angiogenin promoter.